Thinking According to Vygotsky - Rubtsov V.V. (Moscow State University of Psychology and Education, 2021)
November 17, 2021 marks the 125th anniversary of the birth of Lev Semenovich Vygotsky, a brilliant scientist who created something more than a new approach in domestic and world psychology. In the system of concepts of cultural and historical theory, L.S. Vygotsky, in fact, was given a special way of thinking that allows us to reveal the sources of origin, the historical logic of the development of specifically human in man. This way of thinking makes fundamental adjustments to the image of a person that is created by the combined efforts of the entire complex of sciences about him, and not just psychology. Vladimir Petrovich Zinchenko, the first editor-in-chief of the journal "Cultural and Historical Psychology" (this year he would have turned 90 years old), liked to repeat that two psychologists of the XX century - Zh. Piaget and L.S. Vygotsky have reserved a place in the XXI century. Indeed, both of them brought their own view and a special way of thinking to the science of man, which go beyond the limits of known scientific descriptions.